Bio-ethanol production from sweet potato using co-culture of saccharolytic molds (Aspergillus spp.) and Saccharomyces cerevisiae MTCC170 - KUMAR, A.; SADH, P. K.; KHA, SURE; DUHAN, J. S. (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2016)
In the present study, sweet potato which are in abundance and do not interfere with food security was subjected to simultaneous saccharification and fermentation process by co-culture of Aspergillus spices and Saccharomyces cerevisiae.